Prevalence and antibiotic susceptibility of isolated acinetobacters from blood culture in shariati hospital - a rasti; y Erfani; h yazdanbod (Tehran University of Medical Sciences, 2010)
Background and Aim: Acinetobacters are opportunistic pathogens and one of the important agents of nosocomial infections that causes many infections like septicemia and  pneumonia. For resistance to antibiotics acinetobacters are mentioned as a healthcare system complications and are transmitted by the hands of healthcare workers. This research has performed in order to determine prevalence and antibiotic susceptibility of isolated acinetobacters from blood cultures. Material and methods: This study was  performed during a nine months period in  shariati hospital. All 750  positive  blood cultures were distinguished and prevalence of acinetobacter and antibiotic susceptibility of isolated acinetobacters were determined  using disk diffusion agar method. Data were analyzed using SPSS software . Results: According to our findings,133 blood cultures were positive for acinetoloacters(17.7% of cases). The most observed cases were isolated  from emergency ward of hospital (65.5%). Antibiogram  results  using  ciprofloxacin ,cotrimoxasol,gentamicin, ceftazidime, amikacine, tobramicine and ceftriaxone, showed maximum  sensitivity to ciprofloxacine(91%) and  cotrimoxazole (57.5%) and  maximum  resistance to ceftriaxone respectively. Discussion and Conclusion: Because the most acinetobacter  isolation was from emergency ward of hospital, it seems that a part of such infections is more due to contamination than real infection. Therefore it is  recommended  that a prospective cohort study considering standard  and sterile conditions  during  sampling , by  considering  patients clinical features  has to  be performed.